2021
DOI: 10.1007/s40145-021-0494-x
|View full text |Cite
|
Sign up to set email alerts
|

Forsterite-hydroxyapatite composite scaffolds with photothermal antibacterial activity for bone repair

Abstract: Bone engineering scaffolds with antibacterial activity satisfy the repair of bacterial infected bone defects, which is an expected issue in clinical. In this work, 3D-printed polymer-derived forsterite scaffolds were proposed to be deposited with hydroxyapatite (HA) coating via a hydrothermal treatment, achieving the functions of photothermal-induced antibacterial ability and bioactivity. The results showed that polymer-derived forsterite scaffolds possessed the photothermal antibacterial ability to inhibit St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…[58][59][60] Silicatebased 3D printed bioceramics (using forsterite, b-TCP, hardystonite, diopside) have revealed antibacterial properties against S. aureus, S. epidermidis and E. coli. [61][62][63][64][65] However, to the best of our knowledge, neither b-Ca 2 SiO 4 bioceramic fabricated by UV-LCD from a mixture of light-sensitive preceramic polymer resins nor its antibacterial activities have been reported to date. Building on the above concept, this study presents an innovative approach to the fabrication of porous b-Ca 2 SiO 4 scaffolds by UV-LCD, using two different preceramic resins.…”
Section: Papermentioning
confidence: 99%
“…[58][59][60] Silicatebased 3D printed bioceramics (using forsterite, b-TCP, hardystonite, diopside) have revealed antibacterial properties against S. aureus, S. epidermidis and E. coli. [61][62][63][64][65] However, to the best of our knowledge, neither b-Ca 2 SiO 4 bioceramic fabricated by UV-LCD from a mixture of light-sensitive preceramic polymer resins nor its antibacterial activities have been reported to date. Building on the above concept, this study presents an innovative approach to the fabrication of porous b-Ca 2 SiO 4 scaffolds by UV-LCD, using two different preceramic resins.…”
Section: Papermentioning
confidence: 99%
“…The antibacterial efficiencies of the scaffolds against S. aureus and E. coli were enhanced by 96.1% and 95.6%, respectively. 85 A customized photothermal MXene-based hydrogel scaffold (GelMA/-TCP/sodium alginate (Sr 2+ )/MXene (Ti 3 C 2 ) (GTAM) hydrogel) was developed by using 3D printing. Invitro analysis showed that the GTAM scaffolds were able to inhibit the growth of Gram-positive and -negative bacteria via NIR light.…”
Section: Near-infrared (Nir) Light Photothermal Therapy (Ptt)mentioning
confidence: 99%
“…The polymer-derived forsterite scaffolds were found to possess the photothermal in- vitro antibacterial capability under 808 nm laser irradiation to inhibit S. aureus and E. coli growth. The antibacterial efficiencies of the scaffolds against S. aureus and E. coli were enhanced by 96.1% and 95.6%, respectively …”
Section: Antimicrobial 3d-printed Scaffoldsmentioning
confidence: 99%
“… Antibacterial mechanisms of scaffolds Bacteria used for antibacterial assays Ref. Surface charge Chitosan/zoledronic acid/nano hydroxyapatite scaffold; chitosan/zein/silica scaffold Positively charged surface disrupting the negatively charged membrane of bacteria; Covering bacterial cell wall to block transport; Penetrating bacterial cell wall to prevent DNA replication E. coli , S. aureus [ [100] , [101] , [102] ] Pressure (surface charge) Potassium-sodium niobate scaffold; (Ba,Ca) (Ti,Zr)O 3 scaffold Piezoelectric effects inducing surface charge; Surface charge generating micro-electric field and ROS around the material to kill bacteria E. coli , S. aureus [ 38 , 94 ] Photothermal effect Free carbon-containing forsterite scaffold; Forsterite-hydroxyapatite scaffold Photothermic effect generating ROS and increasing temperature to kill bacteria S. aureus , E. coli , MRSA [ 22 , 99 , 103 ] Magnetothermal effect Mg 2 SiO 4 –CoFe 2 O 4 scaffold Magnetothermal effect generating thermal energy and increasing temperature to kill bacteria S. aureus , E. coli [ 95 , 104 ] Sonodynamic effect Palacos (bone cement) scaffold Attaching to certain cellular components and inducing damage under ultrasound irradiation; Generating ROS inducing oxidative damage to the cell wall MRSA, S. aureus , E. Coli, P. aeruginosa [ [105] , [106] , [107] ] Photocatalysis GDY-modified TiO 2 nanofiber s...…”
Section: Bioceramic-based Scaffolds With Physical Antibacterial Funct...mentioning
confidence: 99%